Analysis of parahippocampal gyrus in 115 patients with hippocampal sclerosis - Ferreira,Nelson Fortes (2003)
PURPOSE: Analysis of the parahippocampal gyrus (PHG) involvement in 115 patients with hippocampal sclerosis (HS) by MR imaging. The simultaneous occurrence of ipsilateral fornix (F) and mamillary body (MB) volume loss was checked also. These findings were correlated with the side of hippocampal involvement, the sex, patient´s age, and the symptoms onset. METHOD: The MR images of 115 patients with HS were studied retrospectively. All the examinations were performed on 1.5 T units (SIGNA, GE, Milwaukee, WI) and included high resolution coronal T2-weighted images (3 mm thickness, 0.6 mm gap). RESULTS: The patient's age ranged between 3.5 and 80 years (mean 34.1); 62 (53.9%) were female and 53 (46.1%) were male. There were HS on the left side in 53 (46.0%), on the right side in 51 (44.3%), and bilateral in 11 (9.7%). In 43 (37.3%) cases there were ipsilateral PHG volume loss and signal hyper intensity on T2-weighted imaging. In 29 (25.2%) cases there were ipsilateral fornix volume loss and in 10 (34.5%) of this there were also ipsilateral MB changes. In abnormal PHG, 23 (53.4%) were on the left side, 17 (39.5%) were on the right side, and 3 (7.1%) were bilateral. There were fornix changes in 15 (34.8%) cases and MB volume loss in 5 (11.6%) cases. Pertinent clinical data were obtained in only 18 (41.8%) of the PHG lesion cases and 11 (61.1%) of these patients had epileptic attacks for more than 20 years before the examination. CONCLUSION: PHG involvement must be investigated in patients with HS and we suggest that the term mesial temporal sclerosis should be used only if there are also changes at this anatomical site.